Interactive Visualization of Three-Dimensional Segmented Images for Neurosurgery - Katz, William T.; Snell, John W.; Hinckley, Ken (1995)
Visualization for neurosurgical applications requires speed, realism, and methods for unobtrusive and intuitive interactive exploration. The method presented here uses fast voxel projection to multiple compositing buffers together with a hybrid user interface which includes six degree-of-freedom props.